Direct detection of toxigenic Bacillus cereus in dietary complement for children and cassava starch (2014)
ABSTRACT : Bacillus cereus is a food contaminant and a known human pathogen that can cause emetic and diarrheal syndromes. In this study we evaluated the presence of toxigenic B. cereus by multiplex PCR directly in dietary complement for children and cassava starch samples collected on Medellin, Colombia. Of 75 dietary complement for children samples evaluated, 70.7% were contaminated with toxigenic B. cereus and four different toxigenic consortia were detected: I: nheA, hblC, cytK (9.8%), II: nheA, hblC (2%), III: hblC, cytK (41.2%), IV: hblC (47%). Of 75 cassava starch samples, 44% were contaminated with toxigenic B. cereus and four different toxigenic consortia were determined: I: nheA, hblC, cytK (48.5%), II: nheA, hblC, cytK, cesB (3%), III: hblC, cytK (30.3%), IV: hblC (18.2%). In general, in dietary complement for children only enterotoxigenic consortia were detected while in cassava starch the enterotoxigenic consortia predominated over the emetic. Multiplex PCR was useful to detect toxigenic B. cereus contamination allowing direct and simultaneous detection of all toxin genes in foods. This study is the first in Colombia to evaluate toxigenic B. cereus, providing information of importance for microbiological risk evaluation in dried foods.